Impact of Classroom Management on students’ Academic Achievement at Secondary School Level in Peshawar (Journal of Social Sciences Review, 2023)
This research paper was to determine the impact of classroom management on student’s academic achievement at the secondary school level in Peshawar. The study population comprised all secondary school teachers in Peshawar. The sample of the study was 240 Secondary School teachers, which were randomly selected. Students’ achievement scores were obtained from the class IX annual examination results of BISEP. The data was analyzed through the Pearson coefficient of correlation, and regression analysis was used to test of hypothesis. The study found a positive relationship between classroom management & students' achievements. It was also found that Teaching Learning Process and students' achievements were a positive relationship. It was confirmed that Classroom Rules play a positive role in the achievement level of the students. It was also indicated that rewards & punishments contribute towards the student's achievements. The study suggested that future researchers may take up the issue of classroom management at various other levels as well.
Keywords: Classroom Management; Teaching Learning Process; Classroom Rules; Reward & Punishment; Students’ Academic Achievement